The Relationship Between The Use Of Powerpoint Media And Motivation In Sociology Course In Paket C Equivalency Program - Mona Apriana Sibarani; Solfema Solfema (Universitas Negeri Padang, 2022)
This research is motivated by the low motivation to learn sociology of learning citizens when attending equivalence education package C at SPNF SKB Region II Padang City. One of the causes is the use of powerpoint media which is rarely used by tutors when doing learning. Therefore, a study was conducted to see the relationship between the use of PowerPoint and the learning motivation of the residents studying there. The purpose of this study is to describe the use of powerpoint media in SPNF SKB Region II Padang City, to describe the motivation to learn sociology of learning citizens on equivalence education package C in SPNF SKB Region II Padang City, and to see the relationship between powerpoint media use and motivation to learn sociology. at SPNF SKB Region II Padang City. The type of research used is quantitative with correlational methods. The population of 56 people and a sample of 23 people were taken from residents studying in equivalence education package C at SPNF SKB Region II Padang City. The research data obtained were processed using percentage and product moment analysis techniques. The results of the study show that: 1) the description of the use of powerpoint media in equivalence education in package C is still relatively low; 2) the description of the learning motivation of learning citizens in the equivalence education package is still relatively low; and 3) there is a significant relationship between the use of powerpoint media and the learning motivation of citizens to learn equivalence education package C in SPNF SKB Region II Padang City.Keywords: Learning Media, powerpoint, learning motivation